Aplikasi Metode EOQ Dalam Efisiensi Total Biaya Persediaan dan Optimasi Pengendalian Persediaan Bahan Baku Thinner di PT. XYZ - Arya Pramandeva Putra; Jauhari Arifin; Daniel Parlindungan (Fakultas Teknik, 2023)
Raw material procurement policies play an important role in the production activities of a company. In order to maintain customer trust, PT. XYZ is very concerned about the quality and timeliness of the products it produces. This research was conducted to analyze raw material procurement policies and apply the Economic Order Quantity (EOQ) method which is considered effective as a measure to optimize inventory control efforts and minimize total inventory costs. This study shows that the total inventory cost (TIC) using EOQ has a more economical amount of Rp. 150,080, compared to the TIC resulting from company policy, namely Rp. 967,671. The EOQ model also takes into account the economical purchasing process which is carried out 5 times a year with a purchase quantity of 239 units per order, reorders are made when the remaining stock is 44 units and safety stock is 32 units. In order to maximize the inventory function, the maximum stock or limit on the availability of stock in the warehouse is also taken into account, which is 277 units.